Ultrasound evaluation of caesarean section uterine scar and its correlation to intraoperative scar thickness - Leelapalli, Anusha; Priyadarshinee, Barsha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The number of caesarean sections performed has skyrocketed in recent decades. The most frequent indication for a caesarean section is a previous caesarean birth. The goal of the current study was to compare the lower uterine scar thickness in pregnant with history of previous caesarean delivery as determined by sonography with the actual scar condition at the time of surgery. Methods: The study involved 100 pregnant women between gestational age of 35 completed weeks and 38 weeks with history of previous caesarean delivery and were attended to OPD for antenatal checkups in the department of obstetrics and gynaecology, SCBMCH, over a period of one year from 1st June 2019 till 31st June 2020. Who underwent transabdominal ultrasonography. The lower uterine segment [LUS] thickness was measured by measuring the interphases between the myometrium, the Chori amniotic membrane, and the bladder wall. The patients were followed up and correlated ultrasound findings of lower uterine segment thickness with intra-operative finding of lower uterine segment thickness. Pearson correlation is the statistical method used to measure correlation. Results: Correlation of ultrasound scar thickness and intra-operative scar thickness was evaluated by correlation coefficient (r value) i.e., 0.405 and p value i.e., 0.001. Conclusion: According to the current study, decreased uterine scar thickness, as determined by sonography, is a reliable indicator of scar defect in women who have had prior caesarean operations. Thus, sonographic measurement of the thickness of the lower uterine segment can properly assess scar status and the choice to offer women a trial of vaginal birth and precautions can be taken.